2022
DOI: 10.1177/11779322221115665
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of the Bioactive Profile and Metabolites of Satureja nepeta in Diseases Related to the Excessive Production of Interleukin-6

Abstract: Inflammatory bowel diseases are caused by an abnormal reaction of the immune system, which becomes hyperactive because the mechanisms responsible for regulating it get out of control. For an effective immune response, many proinflammatory cytokines are secreted, particularly interleukin-6 (IL-6) keystone cytokine inflammation. Many synthetic and natural compounds targeting IL-6 have been studied. The genus Satureja of the Lamiaceae family is generally known for its many virtues, in particular anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…This interaction involved one conventional hydrogen bond, one Van der Waals interaction and one Pi-sigma bond in the active site ( Figure 6 ). IL-6, also known as interferon β2, is a key cytokine in the regulation of inflammation and is produced in response to infections [ 53 ]. It is also involved in the pathogenesis of rheumatoid arthritis [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction involved one conventional hydrogen bond, one Van der Waals interaction and one Pi-sigma bond in the active site ( Figure 6 ). IL-6, also known as interferon β2, is a key cytokine in the regulation of inflammation and is produced in response to infections [ 53 ]. It is also involved in the pathogenesis of rheumatoid arthritis [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that quercetin, catechin, and gallic acid from Satureja nepeta extract exhibited a strong affinity with IL-6R with binding energy values of −7.1, −6.1, and −5.3 kcal/mol, respectively. It was suggested that the interaction with the active site of IL-6R could be a suitable mechanism for the inhibition of IL-6 by S. nepeta polyphenols [ 53 ]. It was recently noticed that genistein showed an excellent binding energy (−10.59 kcal/mol) with IL-6/IL-6Rα of the STAT3 pathway and could therefore inhibit the IL-6/STAT3 pathway by blocking the interaction of IL-6 with IL-6R [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In response to this emerging challenge, the scientific community has turned to innovative approaches, particularly bioinformatic applications, to unravel the complex interplay between exercise, IL-6, and inflammation. Bioinformatics leverages computational tools and techniques to analyze vast amounts of biological data, facilitating a deeper understanding of molecular pathways and interactions [29,30]. Researchers are now using bioinformatics to explore the intricate mechanisms through which heavy exercise influences IL-6 levels and subsequent inflammatory responses [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics leverages computational tools and techniques to analyze vast amounts of biological data, facilitating a deeper understanding of molecular pathways and interactions [29,30]. Researchers are now using bioinformatics to explore the intricate mechanisms through which heavy exercise influences IL-6 levels and subsequent inflammatory responses [29,31]. This multidisciplinary approach enables the identification of potential targets for intervention, paving the way for the development of anti-inflammatory drugs tailored to mitigate the negative consequences of intense physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Adbelkarim et al [59] performed an in-silico analysis of phenolic compounds derived from Moroccan Satureja nepeta, such as quercetin, catechin, and gallic acid, which have a high affinity for the IL-6 receptor, an interleukin that is related to inflammation, apoptosis, and cell differentiation. In addition, it has been shown to have an important role in neurodegenerative diseases [60][61][62].…”
Section: Metabolism Of Phenol Compoundsmentioning
confidence: 99%